Analysis of Real-Time Early Warning Algorithm of Environmental Risk of Air Pollutants Based on Computer Simulation Technology - Rao, Yongcai; Feng, Chunli (Mobile information systems, 2022)
In order to monitor the air pollutants in the living environment in real time, the computer simulation technology is used to monitor the air pollutants, and the weighted algorithm is used to warn the pollutants exceeding a certain content, so as to facilitate the air quality control. Air is an essential element for everyone’s survival. With the development of manufacturing industry, air quality has deteriorated sharply, which has a certain impact on human ecological environment and does harm to residents’ health. When more and more attention is paid to environmental problems, the state has issued corresponding measures to monitor air quality and formulate air quality indicators. Once an element in the air is found to exceed the standard, an alarm will be issued, which is convenient for management and detection. This study analyzes the risk early warning algorithm of pollutants in the air through computer simulation technology to realize the management of air quality. Lay the foundation for human living environment in the future.